EDUKASI PENERAPAN PRINSIP SYARIAH TERHADAP DRIVER ONLINE FOOD DI WILAYAH PENGASINAN - Ridwan Ramadhan; Rizal Fahlevi; Rafika Rahmawati (An-Nizam, 2022)
The ethics of sharia principles are often ignored by humans, sometimes we still have bad behavior towards others, the values that have been taught according to religion must be applied in our daily lives. Food online motorcycle taxi drivers are like a profession whose job is to provide services to take and deliver orders from online food-selling restaurants to customers who buy the food. Sometimes online food motorcycle taxi drivers are still negligent in their activities to behave honestly at work. The ethical values that must be applied by drivers by being friendly and honest with buyers are the core of the author's problems in writing this journal, so the authors make socialization activities in the salting area which aims to make drivers always apply sharia principles. By prioritizing honesty and not lying. The method used by the author is to make observations and also socialize about the honesty of Online Food Drivers.